INDEKS GLIKEMIK DAN SERAT MI SUBTITUSI TEPUNG JEWAWUT DAN BERAS MERAH - Sukmawati Sukmawati; Adriyani Adam; Andi Nur Syamsi AS (Media Gizi Pangan, 2022)
ABSTRACT The problem of diabetes mellitus (DM) needs to get more serious attention because it is the number third killer disease in Indonesia. Barley and brown rice as substitutes for wheat flour in the manufacture of dry noodles are an effort to reduce the glycemic index (GI) and increase the fiber content in noodles. The purpose of this study was to determine the GI value, fiber content and acceptability of noodles substituted with barley flour and brown rice. This research is an experimental research type. The glikemik Indek (GI) test is calculated by comparing the area of the glucose response curve for the test food and the standard food. The results of the organoleptic test on acceptability were tabulated in the table and analyzed using the SPSS computer program, namely the Kruskal-Wallis test with the Mann-Whitney follow-up test and the fiber content test using the crude fiber method. The results of the acceptability test of millet noodles and brown rice from the best taste aspect were F2, F1 texture aspect, F1 color aspect and F1 aroma aspect. The highest total score for the panelists' acceptance test was F1 with a score of 414 points. Formula F1 was used in the test of GI value and fiber content. The GI of the noodles substituted with barley flour and brown rice is 67 (medium) and the fiber content is 16,355 g/100 g. The acceptability of the aspects of taste, texture, color and aroma was highest at the concentration of F1 20% barley flour, 5% rice flour and 75% wheat flour, noodles substituted with barley flour and brown rice with a medium GI value (67) and fiber content of 16.355 g/100 g. Keywords : Brown Rice, Glycemic Index, Barley, Noodles, Fiber ABSTRAK Masalah penyakit diabettes melitus (DM) perlu mendapatkan perhatian lebih serius karena penyakit pembunuh nomor ketiga di Indonesia. Jewawut dan beras merah sebagai pensubstitusi tepung terigu dalam proses pembuatan mi kering. Hal ini menjadi salah satu upaya dalam menurunan nilai indeks glikemik (IG) dan menigkatkan kandungan serat yang terdapat di dalam mi. Tujuan penelitian ini adalah untuk mengetahui nilai IG, kadar serat dan daya terima mi subtitusi tepung jewawut dan beras merah. Penelitian ini merupakan jenis penelitian eksperimental. Uji Indek glikemik (IG) dihitung dengan membandingkan luas kurva respon glukosa pangan uji dan pangan standar. Hasil uji organoleptik terhadap daya terima ditabulasi dalam tabel dan dianalisis menggunakan program komputer SPSS yaitu uji Kruskal-wallis dengan uji lanjutan Mann-Whitney serta untuk uji kadar serat dianalisis menggunakan metode crude fiber. Hasil uji daya terima mi jewawut dan beras merah dari aspek rasa yang terbaik adalah F2, aspek tekstur F1, aspek warna F1 dan aspek aroma F1. Total skoring tertinggi uji daya terima panelis adalah F1 dengan nilai skor 414 poin. Formula F1 digunakan dalam uji nilai IG dan kadar serat. IG mi subtitusi tepung jewawut dan beras merah adalah 67 (sedang) dan kadar serat 16,355 g/100 g. Daya terima aspek rasa, tekstur, warna dan aroma tertinggi pada konsentrasi F1 20% tepung jewawut, 5% tepung beras dan 75% tepung terigu, mi subtitusi tepung jewawut dan beras merah dengan nilai IG  kategori sedang (67) dan kadar serat 16,355 g/100 g.Kata kunci : Beras Merah, Indeks Glikemik, Jewawut, Mi, Serat